Dental negligence: It is time to overcome it - Shail Kumari; Sunil Kumar Mishra; Ramesh Chowdhary (Wolters Kluwer Medknow Publications, 2020)
Dentistry is an honorable profession, but the relationship between the patient and the dentist has changed drastically in the last 20 years. Anxiety has risen in the community and dental profession due to patients' increased tendency to file legal cases against dentists. Thus, awareness of ethics and medicolegal matters is essential for every dental practitioner. This review was conducted to find exact literature related to dental negligence, dentist awareness of negligence, dental consent, and the Consumer Protection Act. An attempt has also been made to inform dentists that they must follow certain protocols to avert lawsuits due to illegal and/or negligent dental practice. In December 2019, the PubMed, Medline, and EBSCOhost databases were electronically searched for published literature, and 648 articles were screened. A manual search was also conducted to retrieve articles of interest. Titles and abstracts related to the topic of interest and available in English were screened and included in the study. Patient consent must be obtained in written before any treatment procedure. Dentists must be aware of dental negligence, as well as the laws governing it, and should be insured under professional indemnity insurance ("defense costs"). In the event of legal proceedings, this provides protection and financial support for case settlement and other expenses.